Key dimensions to strengthen primary care in Peru to forty years of Alma Ata - Cuba-Fuentes, María Sofia (2018)
Peru is a middle-income country, with a fragmented health system. To strengthen the health system based on primary health care there, are key dimensions that must be analyzed: governance, financing, human resources, accessibility, longitudinality, comprehensiveness, coordination, equity, efficiency and quality. The achievement of the development of these dimensions can lead to guarantee a strong primary health care, with improvements in the health of people.